The Prothrombotic Tendency in Metabolic Syndrome: Focus on the Potential Mechanisms Involved in Impaired Haemostasis and Fibrinolytic Balance - Isabella Russo (Scientifica)
The metabolic syndrome is a clinical disorder characterized by impairment of glucose metabolism, increased arterial blood pressure, and abdominal obesity. The presence of these clinical features exposes patients to a high risk of atherothrombotic cardiovascular events. The pathogenesis of atherothrombosis in the metabolic syndrome is multifactorial, requiring a close relationship among the main components of the metabolic syndrome, including insulin resistance, alterations of glycaemic and lipid pattern, haemodynamic impairment, and early appearance of endothelial dysfunction. Furthermore, haemostatic alterations involving coagulation balance, fibrinolysis, and platelet function play a relevant role both in the progression of the arterial wall damage and in acute vascular events. The mechanisms linking abdominal obesity with prothrombotic changes in the metabolic syndrome have been identified and partially elucidated on the basis of alterations of each haemostatic variable and defined through the evidence of peculiar dysfunctions in the endocrine activity of adipose tissue responsible of vascular impairment, prothrombotic tendency, and low-grade chronic inflammation. This paper will focus on the direct role of adipose tissue on prothrombotic tendency in patients affected by metabolic syndrome, with adipocytes being able to produce and/or release cytokines and adipokines which deeply influence haemostatic/fibrinolytic balance, platelet function, and proinflammatory state.